RCARS: Residential College Accommodation Rental System for Student Housing Center - MUNIANDY, HEMASRRI; Nurezayana Zainal, (Applied Information Technology And Computer Science, 2025)
RCARS is a web-based Residential College Accommodation Rental System developed for the Student Housing Centre (PRP) of Universiti Tun Hussein Onn Malaysia (UTHM) to address challenges associated with manual accommodation application management. It streamlines the processing of applications, status monitoring, and payments through five main modules. Login and Registration manages user access, while Accommodation Application allows users to submit requests and receive updates. Admin Management oversees applications, packages, hostels, and generates related reports. Payment and Quotation automatically calculate fees and generate receipts, while Room Allocation and Management handles room availability and automate room assignments. Developed using Laravel, HTML, CSS, and JavaScript, RCARS emphasizes usability and operational efficiency. It adopts an incremental prototyping approach, allowing iterative testing and continuous improvement based on user feedback. User acceptance testing indicated high satisfaction in terms of usability, functionality, design, and reliability. By reducing administrative workload and improving overall user experience, RCARS significantly enhances the effectiveness and accessibility of UTHM’s residential accommodation management.